DESIGN AND AERODYNAMIC PERFORMANCE ANALYSIS OF 10 KW HORIZONTAL AXIS WIND TURBINE ROTOR BLADES (Jurnal Mekanikal, 2018)
Design and aerodynamic performance analysis of 10 KW horizontal axis wind turbine (HAWT)rotor blades are carried out. The blade geometry is calculated under consideration that the dragis equal to zero to obtain the optimal blade geometry. Drag effect is included in theoreticalpower coefficient was 0.46 at tip speed ratio of 5.5. This value compared well wirh available researchÂ  data. The experimental model had been built and tested using a low speed open circuit wind tunnel. The validation of the theoretical results has bern conducted at single low-tip-speed ratio. The study between theoretical result and the experimentally measured performance. in the torque and power coefficient region for one value of tip speed ratio resulted in good agreement
Keywords: Wind power; wind turbine; rotor blades. power coefficient; torque coefficient; efficitncy.